Molecular characterization of carbapenem and ceftazidime-avibactam-resistant Enterobacterales and horizontal spread of blaNDM-5 gene at a Lebanese medical center - Sobh, Ghena; Araj, George F.; Finianos, Marc; Sourenian, Tsolaire; Hrabak, Jaroslav; Papagiannitsis, Costas C.; Chaar, Mira El; Bitar, Ibrahim (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction In the battle against multidrug-resistant bacterial infections, ceftazidime- avibactam (CZA) stands as a pivotal defense, particularly against carbapenemresistant (CR) Gram-negative pathogens. However, the rise in resistance against this drug poses a significant threat to its effectiveness, highlighting the critical need for in-depth studies about its resistance mechanisms. Methods This research focuses on the genomic characterization of CR- and CZA-resistant Escherichia coli (n=26) and Klebsiella pneumoniae (n=34) strains, harboring the blaNDM and/or blaOXA-48-like genes, at a major Lebanese tertiary care medical center, using whole genome sequencing (WGS). Results Our findings revealed a notable prevalence of blaNDM in all K. pneumoniae strains isolates, with 27 of these also harboring blaOXA-48. On the other hand, E. coli strains predominantly carried the blaNDM-5 gene. Whole genome sequencing (WGS) identified a predominance of ST383 among K. pneumoniae strains, which possessed a multi-replicon IncFIB-IncHI1B plasmid harboring the blaNDM-5. Additionally, various Inc group plasmids in K. pneumoniae across multiple sequence types were found to carry the blaNDM. Similarly, diverse STs of E. coli were observed to carry blaNDM-5 on different plasmids. Discussion The study underscores NDM carbapenemases as a paramount resistance mechanism in Lebanon,jeopardizing critical last-resort treatments. It also illuminates the role of varied sequence types and mobile genetic elements in the spread of NDM resistance,stressing the urgent need for strategies to mitigate this threat, especially in nosocomial infections.